Effects of phosphites on ripening in kiwifruit Hayward - Yommi, Alejandra Karina (2018)
The phosphites (Phi) are inducers of plant defense responses, although also other effects were reported. In kiwifruit (Actinidia deliciosa Hayward), we demonstrated that Phi-treated fruit was more tolerant to gray mold development caused by Botrytis cinerea. The mechanisms are not yet well elucidated. The objective of this work was to evaluate the effect of Phi (30% P2O5, 20% K2O), 0.3% (v/v) on Hayward fruit maturity and quality indexes, by application at different physiological stages of the fruit development: T1) one application at bloom; T2) six weekly Phi applications at the exponential phase of fruit growth; T3) combination of treatments, 1 and 2; T4) control (without Phi). Kiwifruits of all treatments were harvested after physiological maturity (at least 6.2% total soluble solids content, SSC) and were analyzed at harvest in terms of firmness (N), SSC (%), titratable acidity (%) and color (CIELab). Also fruits were evaluated after 4 months of cold storage and shelf-life (7 days at 20°C). Ethylene and carbon dioxide rate production were determined at 20°C in the fruits of all treatments. The experiment was conducted during two consecutive years. The results show that the Phi had an effect on firmness, variation between years, while had no effects on other maturity indexes. Firmness of Phi-treated fruits was higher than control ones at shelf-life, essentially when Phi was applied at the exponential phase of fruit growth. This change in the softening rate was associated with the ethylene production rate that was too affected by some Phi treatments. Phi treatments (T2 and T3) significantly affected the ethylene and respiration rates, reducing significantly the values at the climacteric peak. This result suggests that Phi affects perception or biosynthesis of ethylene, and some of this response may be related to the induction of salicylic acid.